Analisis Information Gathering Target Daftar Pencarian Orang Menggunakan Metodeopen Source Intelligence Pada Kejaksaan Tinggi Aceh - Gunawan, Ferry; Imilda; Keumala, T. M. Mirza (Jurnal Sistem Komputer (SISKOM), 2024)
This research aims to analyze information gathering on wanted list (DPO) targets using the open source intelligence (OSINT) method at the Aceh High Prosecutor's Office. This research focuses on the Google search engine platform and Facebook social media. Before conducting information gathering, a sock puppet account will be created. Information gathering will go through four stages, namely: collection, processing, exploitation, production. At the collection stage, several OSINT techniques will be used, namely: real name techniques, search engine techniques, and social network techniques. Then, entering the processing stage, the information will be validated and made more useful. At the exploitation stage, existing information is analyzed in depth and eliminates information that is less useful. The production stage will describe in detail the personal information obtained and processed. From these results, the target's personal information is obtained such as full name, profile photo, domicile, occupation, place of work, vehicle and family relationships. This provides a real picture that the Open Source Intelligence (OSINT) method can make it easier for law enforcers to carry out their duties, especially carrying out searches and finding targets on the People's Wanted List.